EFEK MEDIA ONLINE DUTA DAMAI SUMUT UNTUK MENCEGAH HOAX DI KALANGAN PELAJAR SMA 2 MUHAMMADIYAH MEDAN - Astri Handayani (JISOS: JURNAL ILMU SOSIAL, 2023)
Duta Damai is a community formed by the National Counterterrorism Agency (BNPT) since 2016 which is filled with young generations who are more productive in utilizing technology to carry out positive activities. The BNPT considers that there is a need for a preventive measure to equip students or youth so that they are not contaminated by solicitations or seductions that divide the nation, from unity to unity and with full awareness also seeing today's conditions that on average every child has a gadget. Duta Damai Sumut under the auspices of the BNPT has succeeded in providing positive content through social media that can be accessed easily by teenagers and even all groups. Related to this, researchers chose SMA 2 Muhammadiyah Medan as the object of research. Regarding the solution to the rampant hoaxes in the country, researchers are interested in glancing at the North Sumatra Peace Ambassadors. The results of a temporary search by researchers, Duta Damai Sumut have made a lot of use of online media in preventing hoaxes. According to Duta Damai Sumut, starting from online media or cyberspace, indoctrination from radical sites began to intensify and focus on trust among children who then began to look for groups that agreed with him